2014
DOI: 10.1186/1471-2164-15-19
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of natural antisense transcription to an endogenous siRNA signature in human cells

Abstract: BackgroundEukaryotic cells express a complex layer of noncoding RNAs. An intriguing family of regulatory RNAs includes transcripts from the opposite strand of protein coding genes, so called natural antisense transcripts (NATs). Here, we test the hypothesis that antisense transcription triggers RNA interference and gives rise to endogenous short RNAs (endo-siRNAs).ResultsWe used cloned human embryonic kidney cells (HEK293) followed by short RNAseq to investigate the small genic RNA transcriptome. 378 genes gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 48 publications
3
47
1
Order By: Relevance
“…3C). Endo-siRNAs were reported in various species, including plants (Borsani et al, 2005;Zhang et al, 2012;Li et al, 2013;Yu et al, 2016), fungi (Lee et al, 2010) and animals (Tam et al, 2008;Watanabe et al, 2008;Okamura et al, 2011;Werner et al, 2014;Ling et al, 2016). The mechanism of endo-siRNA maturation from NATderived dsRNA that is understood the most, suggests a Dicer-dependent character of dsRNA processing to short siRNA, followed by Argonaute loading into the molecular silencing machinery, RNA-induced silencing complex (RISC) (Czech & Hannon, 2011;Kwak & Tomari, 2012).…”
Section: Rna Interferencementioning
confidence: 99%
See 1 more Smart Citation
“…3C). Endo-siRNAs were reported in various species, including plants (Borsani et al, 2005;Zhang et al, 2012;Li et al, 2013;Yu et al, 2016), fungi (Lee et al, 2010) and animals (Tam et al, 2008;Watanabe et al, 2008;Okamura et al, 2011;Werner et al, 2014;Ling et al, 2016). The mechanism of endo-siRNA maturation from NATderived dsRNA that is understood the most, suggests a Dicer-dependent character of dsRNA processing to short siRNA, followed by Argonaute loading into the molecular silencing machinery, RNA-induced silencing complex (RISC) (Czech & Hannon, 2011;Kwak & Tomari, 2012).…”
Section: Rna Interferencementioning
confidence: 99%
“…Genome-wide analyses using RNA-Seq and singlestranded RNA-Seq protocols, strengthened by parallel analyses of small RNA or degradome sequencing, were proposed in recent years to expand our knowledge of the NATs involved in the endogenous RNA interference Li et al, 2013;Werner et al, 2014;Yu et al, 2016). These studies revealed that nearly 4% of the Arabidopsis thaliana cis-NATs produce putative endo-siRNAs, and approximately 200 of these endo-siRNAs exhibit relatively high expression levels ≥ 10 RPKM (Reads Per Kilobase per Million mapped reads) (Li et al, 2013).…”
Section: Rna Interferencementioning
confidence: 99%
“…Interestingly, both endo-siRNAs and pachytene piRNAs originate from protein-coding genes that are significantly enriched in antisense transcripts, suggesting that the two branches of RNA interference may be intertwined via common testis-specific effector proteins. 19,36 The molecular basis and genomic background of the mechanism in Figure 2 is explained in more detail in other papers. 33,37 In the first step of the proposed sequence of events (Fig.…”
Section: Improving Selection Filters: Optimizing Part 2 Of the Evolutmentioning
confidence: 99%
“…Plants and brown algae also possess miRNA systems, however all three are considered analogous, having independently evolved following co-option of components of the shared eukaryotic endo-siRNA system (Jones- Rhoades et al 2006, Axtell et al 2011, Tarver et al 2012. Of the three RNAi systems, endo-siRNAs have received the least attention in animals, possibly due to their perceived lesser importance in vertebrates, although a renewed interest appears to be developing (Flemr et al 2013, Werner et al 2014, García-López et al 2014, Svoboda 2014. In fact, the capacity for artificial knockdown of target gene expression by hijacking the machinery of the endosiRNA pathway has long been known to be an effective strategy for experimental RNA interference in some vertebrate cell types (Wianny and Zernicka-Goetz 2000, Svoboda et al 2000, Elbashir et al 2001.…”
Section: Rnai Evolution and Functionmentioning
confidence: 99%